Mediating effects of depression on sleep disturbance and frailty in older adult type 2 diabetes patients in the community - Chen, Xushu; Liu, Mengdan; Ma, Qin; Liu, Xin; Peng, Xueping; He, Changjiu (Frontiers in Public Health, 2023)
Introduction: With the progressive aging of the population, frailty is now a significant challenge in geriatrics research. A growing amount of evidence suggests that sleep disturbance and depression have independent effects on frailty, although the underlying mechanisms are not yet clear. This study aimed to investigate the mediating role of depression in the relationship between sleep disturbance and frailty in elderly patients with type 2 diabetes (T2DM) in the community. Method:Purposive sampling was used to collect face-to-face data from 342 community-dwelling T2DM patients in Chengdu, Sichuan Province, China, between February and May 2023. The Pittsburgh Sleep Quality Index (PSQI) scale was used to evaluate sleep quality, the Simple Geriatric Depression Scale (GDS-15) was used to evaluate depressive symptoms, and the FRAIL Scale (FRAIL) was used to evaluate frailty. Linear regression equation and bootstrap self-sampling were used to verify the mediating role of depressive symptoms in sleep disturbance and frailty. Result: The study found that sleep disturbance had a direct positive effect with frailty (β = 0.040, 95% CI:[0.013, 0.069]). Additionally, depression had a direct positive effect on frailty (β = 0.130, 95% CI:[0.087, 0.173]), and depression was found to partially mediate the relationship between sleep disturbance and frailty. Conclusion: Poor sleep quality and frailty are common in patients with T2DM. To reduce the frailty of elder T2DM patients, all levels of society (government, medical institutions, communities) must pay more attention to mental health. A variety of interventions should be considered to improve sleep quality and depression, which in turn may prevent or control frailty.